Peran Guru Penggerak Terhadap Peningkatan Mutu Pembelajaran di SD Negeri 54 Banda Aceh - Hariyana, Eva; Isa, Muhammad; Maulidar, Maulidar (Journal of Technology and Literacy in Education, 2024)
Teachers are a human component and as a teaching medium as well as an introduction to the learning process and also become all aspects that are very influential and become the main centre in the learning process. Guru Penggerak is part of the Ministry of Education and Culture's flagship programme to realise learning that can carry out the principles of an independent curriculum in learning and be able to realise the profile of Pancasila students. SDNegeri 54 Banda Aceh is one of the primary schools that has a driving teacher, with the driving teacher, the school where the driving teacher is implemented will become a superior school, because the results of the study can prove that the driving teacher is able to improve teacher performance, so that teachers are a little constrained by the current independent curriculum due to the lack of school facilities space and teacher time for training as a driving teacher. One of the research focuses is the obstacles faced by the driving teacher in improving the quality of learning at SD Negeri 54 Banda Aceh. The research method used is qualitative, which allows a detailed description in accordance with the observed phenomena. The results showed that the role of the driving teacher is as the main driver in improving the quality of learning at SD Negeri 54 Banda Aceh. With their dedication, passion and commitment, the learning process becomes more effective and meaningful. School facilities have also improved and an inclusive, high-quality learning environment is created. Although faced with obstacles such as time management and understanding the new curriculum, the collaborative efforts and strong commitment of the lead teachers enabled them to overcome these obstacles. The lead teachers are consistently engaged in implementing practices that support learning improvement, reflecting their commitment to improving student learning. Therefore, the role of lead teachers needs to be strengthened and supported on an ongoing basis to continue to advance student achievement and the quality of learning in schools.